Pengaruh Pembelajaran Berdiferensiasi pada Mata Pelajaran IPAS Terhadap Hasil Belajar Siswa - Wardah Wardah; Lukman Hakim; Budi Utomo (Lembaga Bale Literasi, 2025)
This study aims to determine the effect of differentiated instruction on student learning outcomes in the subject of Natural and Social Sciences (IPAS) for Grade IV at SD Negeri 247 Palembang. The background of this research is based on the low student achievement in the topic